What Counts as Foreign Aid: Dilemmas and Ways Forward in Measuring China's Overseas Development Flows. Issue 1 (2nd January 2019) - Sears, Caitlyn
Abstract : The geography of foreign aid is in flux as a growing number of countries from the Global South are entering the field as donors. A principal barrier to understanding this trend is divergence in the definition of aid among emerging market donors and between emerging market donors and traditional donors, as well as transparency in reporting. This article contributes to analysts' toolbox by developing a comparative analysis of aid definitions for China, the largest Global South donor in the world. Using a leading comprehensive database on Chinese aid flows, I construct a scale of definitional restrictiveness for two governmental and three proxy definitions developed by scholars to reconcile aid from non–Organization for Economic Co-operation and Development (OECD) donors with OECD definitions. Based on this analysis, I find that the most inclusive definition of aid does not always translate into the highest aid total estimate. In addition, definitions of aid are moving targets rather than static measures, which can include different flows at different times depending on the state of the global foreign aid system and its major players.